(3GdEeJGY hGdeDGfSIs - (3Ydj Hf eMeO Hf GdYHGS GdJhMjOj, CHh MjGf,J (B400 (3g` s
(3ChdgG (B:s
(3hbGd aj hbJ BNQ(B: (3bO HdZfj Cf GdNGdY aJMSS dj LgOc, hLQO ajgG eMHJc, hCXf GdNGdOj bOeG dCg, hdSJ Bef GHf GdLdHGH s
(3BNQgG (B:s
(3hBNQ eG Cbhd(B: (3CaYd eG JQi, hCVY eG JSJMSf, hGHdZ eG Jghi adjS hGddg efc HO, hdG Yfc Zfi, hGdUHQ Ydjc Cghf ef GdUHQ Yfc dCf GdUHQ Yfc ebQhf HGdjCS s
(3GfXQ GdLRA GdChd HQbe (B60 (3COHs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B326 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B205 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B684s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B2 - (3U (B65 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B167s
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd s
Keywords: (3GdCOHs